KANDUNGAN SENYAWA FLAVONOID DAN AKTIVITAS ANTIOKSIDAN EKSTRAK TEH HIJAU PADA PERLAKUAN SUHU AWAL DAN LAMA PENYEDUHAN - Fajar, Riza Ibnu; Wrasiati, Luh Putu; Suhendra, Lutfi (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI; Vol 6 No 3 (2018): SeptemberDO - 10.24843/JRMA.2018.v06.i03.p02, 2018)
Tea is a kind of plantations which has antioxidant compound and beneficial for health. Based on processing, there 3 kinds of tea namely black tea, green tea, and oolong tea. The aims of this study is to find out the temperature influence and time of brewing toward the flavonoid and antioxidant activity of green tea. This research was conducted to determine temperature and time brewing effect on flavonoid content and antioxidant activity of green tea. The experiment in this study used Randomized Block Design (RBD) with two factors. The first factor was temperature of brewing that consists of temperature 75 o C, 85 o C, and 95 o C. The second factor was the time of brewing namely 5, 10, and 15 minutes. The treatment was repeated twice to obtain 18 units of the experiment. Data were analyzed with analysis of variance, followed by Duncan test. The results showed that the best treatment of green tea extract temperature of 95oC and extraction time 15 minutes resulted in yield 26.2±0,50%, total flavonoids 252.3±1,71 mg QE /g extract and IC50 value was 173.5±1,34 ?g/ml. Keywords :  Green tea, brewing, flavonoid, antioxidant activity